Symbolic nature of Turkestan city and the mausoleum of Khoja Ahmed Yassawi: the experience of field research - Doskhozhina, Zh.; Yessekeyeva, E. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2019)
The article analyzes the sign-symbolic nature understanding of the Mausoleum of Khoja Ahmed Yasawi and Turkestan city by its inhabitants. The research results allowed the authors to conclude that for many Turkestan is not just a sacral place in Kazakhstan, but also a point of contact between Turkic-speaking peoples. In the modern globalizing world, it is a symbol of association and communication. The Mausoleum of Khoja Ahmed Yasawi symbolizes a cultural and religious monument, serves for most people as a place to acquire psychological, spiritual and moral appeasement. In the depth interviewing process, the authors identified main symbolic phenomena of sacral monuments and their role in public consciousness. It was found that the sacred character undergoes a transformation by the influence of globalization processes. Semiotic analysis of Turkestan city and the Mausoleum of Khoja Ahmed Yassawi, based on the experience of field research, reveals that traditions and innovations, religious and historical resurgence of the past are carried out within the framework of public consciousness active modernization. Different understanding of a single “symbol” in the context of globalization can lead to a clash of cultures. Key words: Symbol, Khoja Ahmed Yasawi Mausoleum, Turkestan, Sacred sites, field research